If $ {x^4} + \dfrac{1}{{{x^4}}} = 194 $ , then $ {x^3} + \dfrac{1}{{{x^3}}} $ is equal to
$ \left( a \right){\text{ 76}} $
$ \left( b \right){\text{ 52}} $
$ \left( c \right){\text{ 64}} $
$ \left( d \right){\text{ None of these}} $
Answer
Verified
455.1k+ views
Hint: For solving this type of question we always have to frame the equation in such a way that it will follow the formula which is given by $ {\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab $ . In this we will add $ 2 $ both the sides and framing the equation, we get the value for $ {x^3} + \dfrac{1}{{{x^3}}} $ .
Formula used:
The algebraic formula will be given by
$ {\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab $
Here, $ a\& b $ will be the variables.
Complete step-by-step answer:
We have the equation given as $ {x^4} + \dfrac{1}{{{x^4}}} = 194 $
Now on adding both the sides $ 2 $ , we get the equation as
$ \Rightarrow {x^4} + \dfrac{1}{{{x^4}}} + 2 = 194 + 2 $
Now by using the formula, the left side of the equation will be given as
$ \Rightarrow {\left( {{x^2} + \dfrac{1}{{{x^2}}}} \right)^2} = 196 $
By removing the square from the left sides of the equation, we will get the equation as
$ \Rightarrow \left( {{x^2} + \dfrac{1}{{{x^2}}}} \right) = 14 $
Now again adding $ 2 $ both the sides of the equation, we will get
$ \Rightarrow {x^2} + \dfrac{1}{{{x^2}}} + 2 = 14 + 2 $
Again we can see that the left side of the equation is following the formula $ {\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab $
$ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^2} = 16 $
By removing the square from the left sides of the equation, we will get the equation as
$ \Rightarrow x + \dfrac{1}{x} = 4 $ , and we will name it equation $ 1 $
Now for finding the $ {x^3} + \dfrac{1}{{{x^3}}} $ , we will take out the cube root of the equation $ 1 $ .
$ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^3} = {4^3} $
We get,
\[ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^3} = {x^3} + \dfrac{1}{{{x^3}}} + 3\left( {x + \dfrac{1}{x}} \right)\]
And from this, we will get
$ \Rightarrow {4^3} = {x^3} + \dfrac{1}{{{x^3}}} +3 \times 4 $
And on solving and taking the constant term to one side, we get the equation as
$ \Rightarrow {x^3} + \dfrac{1}{{{x^3}}} = 52 $
Hence, the option $ \left( b \right) $ is correct.
So, the correct answer is “Option b”.
Note: Here, in this question, we can see that with the help of the formula we can easily solve this type of question. So the important thing for us will be to memorize the formula and by practice, we will get the knowledge of substituting the formula with the question. Also while solving the question for the long answer question, we should follow each step.
Formula used:
The algebraic formula will be given by
$ {\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab $
Here, $ a\& b $ will be the variables.
Complete step-by-step answer:
We have the equation given as $ {x^4} + \dfrac{1}{{{x^4}}} = 194 $
Now on adding both the sides $ 2 $ , we get the equation as
$ \Rightarrow {x^4} + \dfrac{1}{{{x^4}}} + 2 = 194 + 2 $
Now by using the formula, the left side of the equation will be given as
$ \Rightarrow {\left( {{x^2} + \dfrac{1}{{{x^2}}}} \right)^2} = 196 $
By removing the square from the left sides of the equation, we will get the equation as
$ \Rightarrow \left( {{x^2} + \dfrac{1}{{{x^2}}}} \right) = 14 $
Now again adding $ 2 $ both the sides of the equation, we will get
$ \Rightarrow {x^2} + \dfrac{1}{{{x^2}}} + 2 = 14 + 2 $
Again we can see that the left side of the equation is following the formula $ {\left( {a + b} \right)^2} = {a^2} + {b^2} + 2ab $
$ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^2} = 16 $
By removing the square from the left sides of the equation, we will get the equation as
$ \Rightarrow x + \dfrac{1}{x} = 4 $ , and we will name it equation $ 1 $
Now for finding the $ {x^3} + \dfrac{1}{{{x^3}}} $ , we will take out the cube root of the equation $ 1 $ .
$ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^3} = {4^3} $
We get,
\[ \Rightarrow {\left( {x + \dfrac{1}{x}} \right)^3} = {x^3} + \dfrac{1}{{{x^3}}} + 3\left( {x + \dfrac{1}{x}} \right)\]
And from this, we will get
$ \Rightarrow {4^3} = {x^3} + \dfrac{1}{{{x^3}}} +3 \times 4 $
And on solving and taking the constant term to one side, we get the equation as
$ \Rightarrow {x^3} + \dfrac{1}{{{x^3}}} = 52 $
Hence, the option $ \left( b \right) $ is correct.
So, the correct answer is “Option b”.
Note: Here, in this question, we can see that with the help of the formula we can easily solve this type of question. So the important thing for us will be to memorize the formula and by practice, we will get the knowledge of substituting the formula with the question. Also while solving the question for the long answer question, we should follow each step.
Recently Updated Pages
Express the following as a fraction and simplify a class 7 maths CBSE
The length and width of a rectangle are in ratio of class 7 maths CBSE
The ratio of the income to the expenditure of a family class 7 maths CBSE
How do you write 025 million in scientific notatio class 7 maths CBSE
How do you convert 295 meters per second to kilometers class 7 maths CBSE
Write the following in Roman numerals 25819 class 7 maths CBSE
Trending doubts
When people say No pun intended what does that mea class 8 english CBSE
In Indian rupees 1 trillion is equal to how many c class 8 maths CBSE
How many ounces are in 500 mL class 8 maths CBSE
Which king started the organization of the Kumbh fair class 8 social science CBSE
What is BLO What is the full form of BLO class 8 social science CBSE
Advantages and disadvantages of science